The roles of transient receptor potential channels in thermostatic behavior, in thermal acclimation, and in tonic immobility in the red flour beetle, Tribolium castaneum (coleoptera: tenebrionidae) - Kim, Hong Geun (Kansas State University, 2014)
Organisms are capable of sensing environmental conditions through diverse mechanisms. Transient receptor potential channels (TRPs) are a cation channel family that has been found to function in diverse sensing mechanisms. In this dissertation, I identified the function of several TRPs in thermosensing and mechanosensing in the red flour beetle, Tribolium castaneum. Candidate TRPs were chosen based on homology to TRPs found and studied in Drosophila melanogaster. To identify the function of candidate TRPs in T. castaneum, I suppressed the expression of target genes by RNA interference technique and investigated the phenotype of each treated beetle. Temperature is a major limiting environmental factor for organisms. I tested the function of candidate TRPs in thermotaxis (behavior) and thermal acclimation (physiology). Using bioinformatics approaches, I identified three candidate TRPs – painless, pyrexia, and trpA1 – involved in high temperature sensing. To test thermotactic behavior, I investigated beetle movement on a temperature arena with two separate temperature zones. Thermal acclimation was tested by pre-exposing beetles to either 42 °C for 10 min. When treated with double stranded RNA of TRPA1 (dstrpA1), the thermotactic response of beetles at 39 and 42 °C was reduced when compared to control groups. With pre-exposure at 42 °C, survivorship of dstrpA1-treated beetles significantly increased after one minute exposure at 52 °C compared to beetles that were not pre-exposed. With dspainless treatment, beetles showed lower response to thermal acclimation and lower long-term survivorship. Beetles treated with dspyrexia showed lower recovery after heat treatment without pre-exposure at 42 °C. To identify the function of candidate TRPs in mechanosensing, I evaluated dsRNA treated beetles for survival, walking behavior, and tonic immobility. Treatment with dsnompC and dstrpA5 resulted in failure in eclosion, causing 93 % mortality in both treatments. Survivors in dsnompC showed defects in elytra sclerotization. In dsnanchung and dsinactive treatments, adults showed abnormal walking behavior and reduced walking speed that were likely caused by defects of mechanosensing in folding of the joint between the femur and tibia. For tonic immobility, beetles with dsnanchung, dsinactive, dswaterwitch and dsick2 (insect cytokine 2) treatments showed increased sensitivity to mechanical stimulation leading to tonic immobility.
Keywords: Tribolium castaneum; Transient Receptor Potential Channel; Thermotaxis; Thermal acclimation; Mechanosensing; RNA interference; Entomology (0353)